Factors contributing to the rheology of tomato puree - Abson, Rachael (2013)
Tomato (Solanum Iycopersicum) puree is created by homogenising the flesh of tomato fruits. The viscosity of this material and the fibrous content is of commercial interest. Tomato puree consists of suspended particles (consisting of whole cells, broken cells and cellular fragments) in an aqueous serum. The contribution of the non-soluble and soluble material to tomato puree rheology was studied with reference to the varying composition of solids and firmness of tomato fruit at four stages of ripeness; mature green, breaker, pink and red ripe. When purees from the red ripe and the breaker fruit with initial total solids contents of approximately 5.5% were diluted to a range of total solids content (between 5 and 1%), both samples decreased in viscosity with total solids. To observe the effect of the serum on tomato puree viscosity, the pellet fraction containing the particles was spun out of the tomato purees by centrifugation so that the particle fraction and the serum could be assessed separately. On further investigation, the viscosity of puree was shown to be affected only to a small degree by the viscosity of the serum. The fact that stirred viscosity was independent of whether the suspension medium constituted of sucrose solution or serum phase showed that little contribution to the viscosity is coming from the soluble hydrocolloids in the tomato sera. Most dominant for viscosity was the particle fraction. The particle fraction was affected by the maturity of the fruit which in turn was associated with changes in fruit texture, particle size and size distribution of the puree. The particles did not behave as rigid spheres, as shown by the large departure from the corresponding Krieger Dougherty fit (Krieger and Dougherty 1959), ripened fruit deviating the furthest. This suggested the more ripened fruit has softer (less rigid) particles, which was shown to have softer tissue before the pureeing process. This may also have made the tissue more susceptible to rupture into smaller particles during pureeing. Quantitative data for size distribution measured by laser light scattering show that as the tomato ripened from green to red, particles were smaller; the mean diameters for the particles in the four puree samples were 893J.lm (mature green), 542J.lm (breaker), 377J.lm (pink), and 262J.lm (red ripe) and of a broader size distribution. Pureed mature green (unripe) fruit were shown to offer more potential as an effective natural viscosifier for foods such as soups and sauces, but they may not meet requirements of taste or colour. The last part of this research (chapter 7) therefore focused on tomatoes with variations in their genes rather than ripeness, harvested at breaker + 7 days. Tomatoes at the same stage of ripeness from the Solanum pennel/ii tomato introgression lines (ILs) were grown and harvested from the glass houses at the University of Nottingham. A screening process was developed to compare the viscosity of small samples of tomato puree from 55 of the ILs, 164 fruits in total; the remaining 21 lines did not produce quantities of fruit sufficient for analysis. The samples were diluted with water to the same total solids of 3.5%. The mean stirred viscosity value for all the lines measured was 132 ± 45 cPo The viscosity was calculated from typically three replicate measurements on three individual fruits per line. Although the particle volume and weight fraction of the puree and the initial total solids content had a strong influence on stirred viscosity, it was shown that the variation between individual fruit was greater than that between the different ILs. Previous texture studies of the IL lines showed marked variations yet there was no clear relationship between the puree viscosities and the expected texture of the whole fruits.